A list of Lepidopterans (Insecta, Lepidoptera) of North Kazakhstan. Part 3. - S. A. Knyzev; I. A. Zuban' (Acta Biologica Sibirica, 2019)
Based on the faunistic studies in North Kazakhstan in 2017-2018, a list of 246 species is given. 124 species are for the first time reported for the North Kazakhstan region